2013
DOI: 10.7903/cmr.11060
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Service Quality in the Banking Industry: A Hong Kong Based Study

Abstract: The goal of this study is to identify the interrelationships between service quality, customer satisfaction and customer loyalty in the retail banking sector in Hong Kong. The study also aims to find out the most important attributes of service quality in retail banks, which can be used to evaluate the characteristics of banking service quality as perceived by customers. A sample of 119 retail banking customers was drawn from the Hong Kong and Shanghai Banking Corporation (HSBC) in Hong Kong. The questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 36 publications
5
98
0
3
Order By: Relevance
“…Ananth et al [51] found that attractiveness, physical facility, and visual appeal could be considered positive indicators of tangibility on customer satisfaction in the banking sector. Furthermore, various researchers have found that there is a positive effect on the relationship between customer satisfaction and tangibility in the banking sector [53][54][55]. Moreover, Krishnamurthy et al [49] and Selvakumar [50] emphasized that tangibility has a positive impact on customer satisfaction in banking services.…”
Section: The Relationship Between Tangibility and Customer Satisfactionmentioning
confidence: 99%
“…Ananth et al [51] found that attractiveness, physical facility, and visual appeal could be considered positive indicators of tangibility on customer satisfaction in the banking sector. Furthermore, various researchers have found that there is a positive effect on the relationship between customer satisfaction and tangibility in the banking sector [53][54][55]. Moreover, Krishnamurthy et al [49] and Selvakumar [50] emphasized that tangibility has a positive impact on customer satisfaction in banking services.…”
Section: The Relationship Between Tangibility and Customer Satisfactionmentioning
confidence: 99%
“…Business services are a general industry, which is unlike any normal manufacturing; it is difficult to standardize the quality of service for service business because it does not only depend on the policy of its enterprises (Angur et al, 1999 Lau et al, 2013), it does not rely on supply chain partners' related services but it also counts on the appreciation of our customers. Therefore, to satisfy the needs of customers and enhance competitiveness, every bussines needs to know how to assess the service quality provided, what factors to or not to meet customer demands, which factors to affect customer perceptions, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, Lau et al (2013) and Saghier & Nathan (2013) claimed that due to the fact that loyalty is related to customer satisfaction, banks performed new affective strategies to improve the quality of service satisfaction and loyalty (Awan, Bukhari, & Anam, 2011). To conclude, Lau et al (2013) and Saghier & Nathan (2013) have identified the dimensions of service quality as the predecessors of customer satisfaction. Many studies have investigated service quality in the retail banking sector in Jordan.…”
Section: Customers' Satisfaction and Loyaltymentioning
confidence: 99%
“…Apparently, the growth of Jordanian economy is greatly influenced by effective banking system. Furthermore, banks experience many challenges in their sectors due to the changing of customers' requirements and to overcome these challenges, it's important for banks to use the most current information technology to advance globally (Lau, Cheung, Lam, & Chu, 2013).…”
Section: Introductionmentioning
confidence: 99%